A Community-Based Intervention: A Hip Hop Framework Toward Decolonizing Counseling Spaces. Issue 2 (3rd April 2021) - Levy, Ian P.; Hess, Courtney W.; Elber, Allison; Hayden, Laura
ABSTRACT: The use of hip hop practices within the minority youth counseling environment have demonstrated patient improvement in areas of critical consciousness and civic mindedness, creativity and activism, and the development of a verbal artistic voice. In this study, hip hop is used as an expressive dance tool that is supportive and congruent with intersectional youth identities, offering a decolonized approach to coping skill development for urban youth. The goal of this qualitative study was to illuminate the perceptions and experiences of youth who engaged in a hip hop dance program in a community center. The results of this study indicate that, through participating in a hip hop dance program, participants experienced: stepping out of their comfort zones, developing increases in self-confidence, and experiencing positive feelings associated with processing difficult topics verbally with their peers. Results highlight the need to honor and integrate youth and cultural practices in future therapeutic interventions.